Neurological Disorders in Adult Celiac Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Celiac disease may initially present as a neurological disorder. Alternatively, celiac disease may be complicated by neurological changes. With impaired nutrient absorption, different deficiency syndromes may occur and these may be manifested clinically with neurological changes. However, in patients with deficiency syndromes, extensive involvement of the small intestine with celiac disease is often evident. There are a number of reports of celiac disease associated with neuropathy, ataxia, dementia and seizure disorder. In these reports, there is no clear relationship with nutrient deficiency and a precise mechanism for the neurological changes has not been defined. A small number of patients have been reported to have responded to vitamin E administration, but most do not. In some, gluten antibodies have also been described, especially in those with ataxia, but a consistent response to a gluten-free diet has not been defined. Screening for celiac disease should be considered in patients with unexplained neurological disorders, including ataxia and dementia. Further studies are needed, however, to determine if a gluten-free diet will lead to improvement in the associated neurological disorder.